Shalom as a Theological Foundation for Reconciliation: Implications for Christian Leadership in Contemporary Indonesian Society - Ronda, Daniel (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2025)
Multi-faceted problems require diverse, creative responses from the church and Christian leaders. Deeper theological engagement is necessary to facilitate the work of reconciliation. This article explores in depth the concept of shalom and its theological reflections in the work of reconciliation. To analyze and address this issue, the researcher employed an appreciative inquiry approach, emphasizing that theology must be developed appreciatively, highlighting not only redemptive theology but also creation theology. The study was conducted in two stages: first, an exploration of the meaning of shalom from a biblical perspective; and second, the construction of theological reflections. The findings of this study are threefold. First, theological reflection on shalom leads the church to view Jesus as the ultimate source of shalom. Therefore, the church is called to strengthen the vertical relationship of its members with God. Second, the church’s concrete actions in the world must be grounded in the values of shalom rather than merely humanitarian agendas. This foundation is rooted in both redemptive and creation theology, working hand in hand to call the church toward restoring human relationships and the created order. Third, the ultimate goal of a shalom community is the realization of justice, love, reconciliation, and hope for the future.